2019
DOI: 10.1002/wcc.571
|View full text |Cite
|
Sign up to set email alerts
|

Indian summer monsoon: Extreme events, historical changes, and role of anthropogenic forcings

Abstract: The South Asian summer monsoon is a complex coupled human-natural system that poses unique challenges for understanding its evolution alongside increasing anthropogenic activities. Rapid and substantial changes in land-use, landmanagement and industrial activities over the subcontinent, and warming in the Indian Ocean, have influenced the South Asian summer monsoon. These might continue to be significant drivers in the near-term along with rising global greenhouse gas emissions. Deciphering the region's vulner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(125 citation statements)
references
References 269 publications
(655 reference statements)
4
121
0
Order By: Relevance
“…us, even if the average trend in sea-surface temperature over the Indian ocean is positive, the spatial distribution of trends does not encourage spatially coherent warm sea-surface temperature (SST) or the organized dynamics necessary for the monsoon [32]. It is further complicated by the changes in land use and land cover [33] and increase or decrease in irrigated land in India which can have local as well as remote effects by altering circulations [34] and increasing concentration of greenhouse gases [2][3][4].…”
Section: Temporal Evaluation Of Rainfall and Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…us, even if the average trend in sea-surface temperature over the Indian ocean is positive, the spatial distribution of trends does not encourage spatially coherent warm sea-surface temperature (SST) or the organized dynamics necessary for the monsoon [32]. It is further complicated by the changes in land use and land cover [33] and increase or decrease in irrigated land in India which can have local as well as remote effects by altering circulations [34] and increasing concentration of greenhouse gases [2][3][4].…”
Section: Temporal Evaluation Of Rainfall and Temperaturementioning
confidence: 99%
“…As large population and growing agriculture sector in South Asia depend on monsoon rainfall patterns, any disruption causes huge concerns. It is vital to explore the response of monsoon dynamics to rising temperature and varying concentrations of greenhouse gases at both scientific and societal level [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent article, Lin and Huybers () explore the implications of gridded products and the underlying network inhomogeneity issues for studying mean and extreme rainfall patterns, using the case of the Indian summer monsoon. A number of studies have identified a long‐term decline in mean precipitation over the core Indian monsoon region (Turner & Annamalai, ) and significant long‐term trends in various metrics of extreme precipitation, as summarized in Singh et al (). A majority of the studies on extreme precipitation rely on the widely used daily, gridded precipitation data sets provided by the Indian Meteorological Department (IMD) at 1° × 1° (Rajeevan et al, ) and 0.25° × 0.25° (Pai et al, ) resolutions, which are derived from rain gauge station records.…”
Section: Lin and Huybers () Findings On Indian Rainfall Trendsmentioning
confidence: 99%
“…Although the IMD data sets are the focus of Lin and Huybers (2018) article, such network inhomogeneity issues exist in most gridded products, which often use the largest number of suitable reporting stations to better capture the spatial variability in climate (e.g., Harris et al, 2014;Schneider et al, 2014). For the Indian domain, substantial differences exist between various precipitation data sets, as demonstrated in Singh et al (2019), for several reasons including their use of a fraction of the IMD rain gauge stations, incorporation of satellite data, different spatial resolutions, and different interpolation techniques. Similar issues and uncertainties associated with a changing observational network have been evaluated and reported for other regional (e.g., Hofstra et al, 2010, for Europe andKing et al, 2013, for Australia) gridded products.…”
Section: Broader Implications and Future Directionsmentioning
confidence: 99%